Changes in expression of Slit1 and its receptor Robo2 in trigeminal ganglion and inferior alveolar nerve following inferior alveolar nerve axotomy in adult rats: a pilot study - Ceber, M.; Mihmanli, A.; Kilic, U.; Sener, U.; Yuksek, A.; Durak, M. A.; Tulubas, F. (My University, 2015)
The objective of this study was to analyze changes in expression pattern of Slit1 and Robo2, and to clarify the relationship between these changes and functional recovery of the axotomized inferior alveolar nerve (IAN) without repair using a rat IAN axotomy model. Slitl and Robo2 were weakly expressed in samples taken from trigeminal ganglion (TG) and IAN of sham surgery rats. In axotomized rats, expression levels increased significantly from day 2 to day 28 post-axotomy, with peaks on days 14 (Slit1) and 7 (Robo2) after axotomy (relative to sham: Slit1 in TG P < 0.0005, Slitl in IAN P = 0.003, Robo2 in TG P < 0.0005, and Robo2 in IAN P < 0.0005). Over-expressed Slitl and Robo2 in both the TG and IANs of axotomized rats did not return to sham levels during the 28-day observation period of this study. The regeneration and functional recovery of axotomized IAN was evaluated by jaw opening reflex (JOR) recorded before and after axotomy. JOR occurrence (0% on day 7, 35% on day 14, and 85% on day 28) increased gradually, and the relative threshold of electrical stimulation eliciting JOR decreased gradually (1000.0 +/- 0.0% on day 7, 854.3 +/- 132.5% on day 14, and 302.6 +/- 92.3% on day 28). On day 28 after axotomy, JOR occurrence and the relative JOR threshold had almost returned to those of sham rats. These findings suggest that Slitl and Robo2 are involved in the regeneration and functional recovery of the axotomized IAN.